Development and evaluation of bromhexine hydrochloride floating microparticulates (Asian Journal of Pharmaceutics (AJP), 2014)
The main objective of the present study is to prepare floating microsphere of the bromhexine hydrochloride in order to achieve gastro-retention which may result in the improvement of bioavailability and solubility as the bromhexineis soluble up to the pH range of 1–4. The microsphere is prepared by the non-aqueous solvent evaporation method using hydroxyl propyl methyl cellulose and ethyl cellulose in different drug polymer ratios.The in vitro release is studied in the USP dissolution apparatus type I.The percentage yield is more than 60% for the all the batches.The entrapment efficiency increased by increasing the polymer concentration and found to be maximum at 1:4 drug polymer ratios.The drug loading was found to be in the range of the 19.30–33.70%. All the batches show in vitro buoyancy percentage in the range of the 53.3% to 70.13% after 12 h. The in vitro dissolution and permeation studies revealed that the formulations followed zero order release pattern and ‘n’ values derived from the PEPPAs equation confirmed that the drug release from the floating system was the non-Fickiantransport mechanism.The SEM studies revealed that the drug adsorbed on the surface of the microspheres can able to provide the burst effect in order to provide the immediate therapeutic effect. Therefore, the floating microspheres were able to be buoyant up to 12 h, having excellent flow properties, and met the required drug release kinetics for gastro-retentive systems.